Hepatitis B virus wild‐type and rtN236T populations show similar early HBV DNA decline in adefovir refractory patients on a tenofovir‐based regimen. Issue 2 (9th July 2012) - Svarovskaia, E. S.; Curtis, M.; Zhu, Y.; Borroto‐Esoda, K.; Miller, M. D.; Berg, T.; Lavocat, F.; Zoulim, F.; Kitrinos, K. M.
<x xml:space="preserve">Abstract</x> Summary. Hepatitis B virus (HBV) pol/RT mutations that confer clinical resistance to tenofovir disoproxil fumarate (TDF) have not been detected to date. In vitro, the rtN236T adefovir dipivoxil (ADV)‐associated resistance mutation confers low‐level cross‐resistance to tenofovir: 3‐ to 13‐fold changes in EC50 from wild type. This study evaluated the clinical response of rtN236T mutant viruses by comparing their early viral load decay kinetics to wild‐type viruses in chronic HBV monoinfected patients harbouring rtN236T prior to initiating TDF or emtricitabine (FTC)/TDF therapy. Baseline samples (n = 105) from adefovir refractory patients were tested for the presence of rtN236T using a highly sensitive allele‐specific PCR assay with an rtN236T detection cut‐off of 0.5%. The rtN236T mutation was detected at baseline in 14.3% (14/98) of analysable patient samples (0.5–93.2%, rtN236T percentage range). The median change in total HBV DNA at week 24 was comparable for patients with rtN236T detected at baseline (−3.7 log10 copies/mL, n = 14) as compared to patients with wild‐type HBV (−3.2 log10 copies/mL, n = 90). In patients with rtN236T, wild‐type and rtN236T mutant virus showed similar rates of HBV DNA decline with no statistically significant difference observed at week 4. Moreover, the proportion of rtN236T remained unchanged in patients in either arm of the study during treatment. In conclusion, the rtN236T mutant virus showed similar HBV DNA decline kinetics to wild‐type virus in adefovir refractory patients who switched to TDF or FTC/TDF. Despite low levels of cross‐resistance in vitro, TDF similarly suppresses wild‐type and rtN236T mutant viruses in vivo.